Expressão de zif-268 durante a aquisição, evocação e extinção de uma memória aversiva - Lemos, Nelson Alessandretti de Mello (2008)
In the behavioral paradigm of discriminative avoidance task, both short and long-term memories have been extensively investigated with behavioral and pharmacological approaches. The aim of the present study was to evaluate, using the abovementioned model, the hippocampal expression of zif-268 - a calcium-dependent immediate early gene involved with synaptic plasticity process - throughout several steps of memory formation, such as acquisition, evocation and extiction. The behavioral apparatus consisted of a modified elevaated plus-maze, with their enclosed arms disposed in "L". A pre-exposure to the maze was made with the animal using all arms enclosed, for 30 minutes, followed by training and test, during 10 minutes each. The between sections interval was 24h. During training, aversive stimuli (bright light and loud noise) were actived whenever the animals entered one of the enclosed armas (aversive arm). Memory acquisiton, retention and extinction were evaluated by the percentage of the total time spent exploring the aversive arm. The parameters evaluated (time spent in the arms and total distance traveled) were estimated with an animal tracking software (Anymaze, Stoelting, USA). Learning during training was estimated by the decrease of the time spent exploring the aversive arm. One hour after the beginning of each section, animals were anaesthetized with sodium-thiopental (i.p.) and perfused with 0.9% heparinized saline solution followed by 4% paraformaldehyde. Brains were cryoprotected with 20% sucrose, separeted in three blocks and frozen. The middle block, containing the hippocampus, was sectioned at 20 micro meters in the coronal plane and the resutant sections were submitted to zif-268 immunohistochemistry. Our results show an increased expression of zif-268 in the dentate gyrus (DG) during the evocation and extinction stages. There is a distinct participation of the DG during the memory evocation, but not during its acquisition. Inaddition, all hippocampal regions (CA1, CA3 and DG) presented an increased zif-268 expression during the process of extinction.